Las necesidades educativas especiales de los estudiantes: un asunto de todos - Ana Herrera-Castro; Giselle Miranda-Cervantes; Marie Clare Vargas-Dengo (Universidad Nacional, Costa Rica, 2004)
Description of the experience generated at Universidad Nacional's Special Education major and of the contributions made by project "UNA's Education for All" during the last six years. The project has helped the students of this university to satisfy their special needs. In order to contemplate the positive value posed by differences in people, we include here the opinions of several social agents that have played a role in the project: a handicap student, a student from the program "Collaboration Hours", an assistant student and a scholar. It is our desire to share their experiences with our readers.